Implementasi Kegiatan Amal Saleh dalam Peningkatan Kecerdasan Spiritual: Studi Kasus di Pondok Pesantren Al Urwatul Wutsqo Bulurejo Diwek Jombang - Hasan, Moch. Sya'roni (Didaktika Religia, 2014)
This study will analyze the implementation of amal saleh at the pesantren alUrwatul Wutsqo, Bulurejo, Diwek, Jombang. The approach in this study is aqualitative case study. The data collection methods were observation, interviewand documentation. To check the validity of the data I will use extension study,perseverance observation and triangulation. The analysis comes up with someconclusions that: 1). Amal saleh planning: determining what should be done,division of tasks, the determination of a group of amal saleh, preparation ofreports 2). The purpose of amal saleh is to enhance dhikr, sincerity, constancy,discipline, and ridlo. 3). Evaluation of charitable activities: Evaluation focused onthe two things: physically: regular report, deposit book activities, monitoring andsupervision. Moderate mental evaluation: tajribah method (testing). Pupils arecontinuously tested for his sincerity. 4). Pupils spiritual intelligence: constancyand not desperate, sincere, God’s intention for the blessing, no wasting time,being responsible, dare to risk, and readiness for mutual assistance.